OS SABERES DA EDUCAÇÃO FÍSICA EM PAUTA: CONTEÚDOS DE ENSINO DA EDUCAÇÃO BÁSICA E CONHECIMENTOS CONSTITUINTES DOS PROCESSOS DE SELEÇÃO PARA INGRESSO NO ENSINO SUPERIOR - Santos, Katiane dos (2014)
The objective of this study is to know about some Physical Education knowledge/contents based on university entrance examinations from State Universities in Paraná and Curricular Pedagogic Proposals from state public schools in Irati city - PR, where it is possible to have a current panoramic view of the subject in this context. Our assumption is Physical Education has had a new space into education and it has had other different meaning. We tried to prove this hypothesis based on historical analysis of the subject through bibliographic and documental review and also based on the context where systematized examinations can be a mean to notice some changes representing new challenges around the subject since for a long time it hasn`t taken any formal evaluative process. It were analyzed the structure and contents regarding Physical Education of the university entrance examination from seven State Universities in Paraná, the High School National Examination - Enem and serial examinations to notice how the contents in these examinations are associated with the contents from the subject during the Basic Education such that the idea of Physical Education is based on Curricular Pedagogic Proposals of each education institution and pedagogical public policies which them in Paraná are State Basic Education Curricular Policy. This study helped to know a little more about the current idea of Physical Education on our state reality. It is possible to emphasize that knowledge on Basic Education is understood as something more homogeneous but contents that are initial requirements to be successful in university entrance examination to study Physical Education at the universities are heterogeneous. Based on our analyses it is possible to highlight the importance of the evaluation regarding the construction of the idea of the subject since only the physical perspective is not enough anymore so it is also necessary the intellectual knowledge to improve the Physical Education